2009
DOI: 10.1097/fbp.0b013e328330dcff
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting as a mediator of the relationship between perceived stress and cigarette smoking status in adolescents

Abstract: There has been a wealth of research providing evidence for the relationship between stress and cigarette smoking during adolescence. Despite this knowledge, little is known about possible behavioral mechanisms by which stress exerts its influence on the decision to smoke. This study sought to examine one such behavioral characteristic, delay discounting, that may mediate the relationship between stress and cigarette smoking. Delay discounting generally refers to the discounting of value for outcomes because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 40 publications
5
49
1
Order By: Relevance
“…The present finding supported the earlier studies done by Booker et al (2007), Fields et al (2009), Yaris (2010 and Slopen et al (2013) who found positive relationships between stress and cigarette smoking behavior and stressed that higher levels of stress would increase the risk of cigarette smoking in adolescents. These results also supported, the social cognitive theory introducing adolescence as a problematic period of heightened stress in life.…”
Section: Discussionsupporting
confidence: 82%
“…The present finding supported the earlier studies done by Booker et al (2007), Fields et al (2009), Yaris (2010 and Slopen et al (2013) who found positive relationships between stress and cigarette smoking behavior and stressed that higher levels of stress would increase the risk of cigarette smoking in adolescents. These results also supported, the social cognitive theory introducing adolescence as a problematic period of heightened stress in life.…”
Section: Discussionsupporting
confidence: 82%
“…The empirical association between perceived stress and smoking among adolescents has been consistent across various populations (Fields et al, 2009; Kim and Park, 2016; Lorenzo-Blanco and Unger, 2015) and robust after controlling for confounding influences (Finkelstein et al, 2006; Siqueira, L. et al, 2000; Sussman et al, 1998). A potential explanation for this association is that adolescents with high perceived stress may turn to tobacco use as a pharmacological means of coping with sources of distress that are otherwise unmanageable.…”
Section: Introductionmentioning
confidence: 82%
“…With regard to impulsive discounting, the prefrontal and subcortical circuits are largely those that have been implicated with discounting decision making in fMRI research (Bickel et al 2009, McClure et al 2004), suggesting that commensurate impairment in discounting may be a behavioral manifestation of these neuroadaptive changes. With regard to the antireward system, the role of stress in discounting has been only modestly studied, and results are mixed (Diller et al 2011, Fields et al 2009, Torregrossa et al 2012, White et al 2008). However, purely from conjecture, given the laboratory evidence on withdrawal effects discussed above, the chronic augmentation of the antireward system may be a further plausible mechanism for increasing discounting.…”
Section: Processes Engendering Reinforcer Pathologymentioning
confidence: 99%